MP005: Treating and Reducing Anxiety and Pain PEDs (TRAPPED 2): time for action - a PERC project. (2nd June 2016) - Trottier, E. D.; Ali, S.; Meckler, G.; Blachet, M.; Stang, A.S.; Porter, R.; Le May, S.; Dubrovsky, A.; Chan, M.; Jain, R.; Principi, T.; Joubert, G.; et al.
Abstract : Introduction: Multiples barriers to appropriate analgesia are reported in the paediatric emergency department (PED), including limited accessibility to effective strategies.Our objective: was to evaluate the improvement in the accessibility of pain and anxiety management strategies in Canadian PEDs, after the creation of a national pediatric pain Quality Improvement Collaborative (QIC), through Pediatric Emergency Research Canada (PERC).Methods: In 2013, the TRAPPED 1 survey was administered to Canadian PEDs, in order to evaluate what resources were in place for pain and anxiety management. A pain QIC was then created to stimulate the implementation of new strategies, through information sharing between PEDs. In 2015, the TRAPPED 2 cross sectional survey was administered. Its focus was to evaluate the improvement in the accessibility of specific strategies reported by each centre, after participating in this QIC, and working to implement change within their own PEDs.Results: All 15/15 Canadian PEDs responded to the TRAPPED 1 survey in 2013 and 11 agreed to participate in the national pain QIC. In-person, phone meetings, follow up surveys and email communications were employed for information sharing. Strategies identified by the QIC to be newly introduced in individual centres were educational initiatives, distraction options, nurse-initiated protocols and intranasal (IN) medications. All 15 PEDs completed the TRAPPED 2 survey. Compared to 2013, an increased number of PEDs used face-based pain scales (14/15 vs 6/15) and behavioural scales (5/15 vs 1/15) for pain assessment in 2015. Use of reminder posters on pain management at triage increased from 4/15 to 6/15 PEDs. Availability of tablets for distraction increased from 4/15 to 10/15 PEDs. Nurse-initiated protocols for topical anesthetic and oral sucrose (for needle procedures) increased from 10/15 to 12/15 sites and from 12/15 to 14/15 sites respectively. Availability of IN medications increased; fentanyl from 9/15 to 14/15 sites and midazolam from 8/15 to 10/15 sites. Ten of the 11 PEDs involved in the QIC strategy reported the implementation of at least one of their own identified strategies.Conclusion: This study suggests that the use of a QIC may improve the introduction of new strategies to reduce pain and anxiety in EDs. QICs may also be helpful to other centres when introducing new strategies.